UJI KELAYAKAN KUALITAS PASIR SUNGAI MAUBESI DENGAN PASIR LUMAJANG TERHADAP KUAT TEKAN BETON DAN KUAT TARIK BETON ( MUTU FC’ 25 MPa) - Handika Setya Wijaya; Blasius Tahik (Universitas Islam Balitar Blitar, 2020)
Aggregate needs in Maubesi, North Central Timor Regency, , as a concrete mixture for the work of construction of natural stone, which has quite a large potential. Research is aimed at; 1) know the characteristics of the statical river in the Maubesi, North Central Timor Regency, and aggregate dulcet from Lumajang; 2) find to uncover of the pressure concrete and the pull that has been generated from the river of North East Timor Regency and the aggregate dulcet of Lumajang; 3) find out the modulus of elasticity of the rivers of the from river in the Middle East North Coast and the Lamajang . This research is a collaborative research on the sample base and analysis of aggregate characteristics and testing of basic conditions and tests interested in and modulus of elasticity. Aggregates Strong pressure from the basement to the beginning until the end is obtained from the 2.747 walk in zone 1 ( fine send ) aggregate North Center of Central Timor, with the strength of Central Timor in the amount of 13,472 MPa ( congrete age ) silkiness of the (concrete age 7 days) , 20,727 MPa (concrete age 28 days), The compressive strength of concrete from the initial age of concrete to the end was obtained from the Maubesi aggregate of North Central Timor with compressive strength of 13,472 MPa (concrete age of 7 days), 20,727 MPa (concrete age of 28 days), and strength Tensile pull of 1,529 MPa (7 days concrete age), 2,352 MPa (28 day concrete age). While the compressive strength of concrete is obtained from the aggregate. Lumajang with compressive strength totaling 18,072 MPa (7 days concrete age), 27,802 MPa (28 days concrete age), and Tensile strength of aggregate rolled concrete. , 3,297 MPa (concrete age 28 days). Modulus of elasticity of the Maubesi North Central Timor aggregate 25677.1 N / mm² while for Lumajang aggregate 25385.9141 N / mm²